2012
DOI: 10.1186/1479-5876-10-184
|View full text |Cite
|
Sign up to set email alerts
|

HLA-E expression in cervical adenocarcinomas: association with improved long-term survival

Abstract: BackgroundCervical cancer is the third most common cancer in women worldwide. The most common histopathological subtype is cervical squamous cell carcinoma (SCC, 75-80%), followed by adenocarcinoma (AC) and adenosquamous carcinoma (ASC; together 15-20%). Rising incidence rates of AC have been observed relative and absolute to SCC and evidence is accumulating that cervical AC is a distinct clinical entity. Cervical SCC, ASC, and AC are caused by a persistent infection with high-risk human papillomavirus (HPV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 45 publications
3
42
2
2
Order By: Relevance
“…In contrast, we did not find significant associations between classical HLA expression and survival rates. Possibly, due to the obvious poor survival of this metastatic patient group, contrary to previous findings, we could not confirm survival advantage for AC patients with HLA-E expression in the primary tumor [24]. …”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…In contrast, we did not find significant associations between classical HLA expression and survival rates. Possibly, due to the obvious poor survival of this metastatic patient group, contrary to previous findings, we could not confirm survival advantage for AC patients with HLA-E expression in the primary tumor [24]. …”
Section: Discussioncontrasting
confidence: 98%
“…Until now only HLA-E was studied in SCC and AC primary cervical cancer samples and high expression of HLA-E was found in 56 %, with significantly higher expression in cervical AC compared to SCC [24]. In contrast, in the present study, we found 30 % expression of HLA-E in the primary tumor for both groups.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Moreover, we also found that both HLA-E and HLA-B expression level were markedly increase in ESCC, nevertheless HLA-E was down regulated in breast cancer (de Kruijf et al, 2010) and glioblastomas (Kren et al, 2011) as a prognostic marker, also weekly expressed in multiple cell line (Marin et al, 2003), exception the higher expression predicted better survival in cervical adenocarcinomas (Spaans et al, 2012) while HLA-B was down-regulated in ovarian cancers (Le et al, 2002). Therefore, HLA-E and HLA-B may have specific function pattern in ESCC.…”
Section: Discussionmentioning
confidence: 88%